2022
DOI: 10.1111/rsp3.12575
|View full text |Cite
|
Sign up to set email alerts
|

Spatial mobility patterns and COVID‐19 incidence: A regional analysis of the second wave in the Netherlands

Abstract: A key policy measure introduced by governments worldwide at the beginning of the coronavirus disease 2019 (COVID-19) pandemic was to restrict travel, highlighting the importance of people's mobility as one of the key contributors to spreading severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, there was little consistency regarding the geographical scale or the severity of these measures. Little use was made of commuting and travel data to inform decisions on when, where and at what level re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…They can be considered to provide very reliable results, especially if one uses a dataset of both companies that cover most of the world. Several studies have demonstrated a strong relationship between COVID-19 cases and people’s mobility, identifying commuting behavior as a spatial determinant of COVID-19 patterns [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. These studies demonstrate the potential of mobility data for understanding population-level movements and identifying areas of high risk.…”
Section: Introductionmentioning
confidence: 99%
“…They can be considered to provide very reliable results, especially if one uses a dataset of both companies that cover most of the world. Several studies have demonstrated a strong relationship between COVID-19 cases and people’s mobility, identifying commuting behavior as a spatial determinant of COVID-19 patterns [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. These studies demonstrate the potential of mobility data for understanding population-level movements and identifying areas of high risk.…”
Section: Introductionmentioning
confidence: 99%
“…Although the COVID-19 pandemic was a global threat, there have been substantial differences across regions in the extent to which they were affected by the pandemic (White and Hébert-Dufresne, 2020;Bosa et al, 2021;Hoekman et al, 2020;Roelofs et al, 2022). Many studies show that preventive practices, such as social distancing, have been one of the main determinants of regional differences in the number of infections and deaths (Badr et al, 2020;Glaeser et al, 2020;Carteni et al, 2020;Engle et al, 2020;Nouvellet et al, 2021;Hadjidemetriou et al, 2020).…”
Section: The Link Between News Media and Health Behaviormentioning
confidence: 99%
“…As shown in Section 4.3.1, the pandemic came in waves, which are also reflected in news reporting. Recent studies show that the determinants of the spread of COVID-19 varied in different phases of the pandemic (Roelofs et al, 2022). This implies that, with each new wave and growing scientific and experiencebased insights, peoples' perceptions and behavioural reactions to the pandemic might have also changed.…”
Section: Empirical Approachmentioning
confidence: 99%